Économies de la pauvreté au Moyen Âge - Benito, Pere; Carocci, Sandro; Feller, Laurent (Collection de la Casa de Velázquez, 2023)
This book proposes a new approach to the topic of poverty in the Middle Ages in Mediterranean Europe (9th-15th centuries) in order to understand the economic and social phenomena that characterized it. The studies gathered here, by French, Spanish and Italian medievalists, aim to go beyond the problems studied in the 1960s and 1980s by Michel Mollat. The process of impoverishment, working poverty, institutional and personal attitudes towards poverty and the material culture associated with it form the basis of the proposed studies. Also examined are the relationships that poverty has with work, the bonds that it forces to form or break and the survival strategies developed by those who, for one reason or another, have fallen into it.